2020
DOI: 10.21203/rs.3.rs-57987/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential effects of Angiotensin-Converting Enzyme Inhibitors and Angiotensin II Receptor Blockers on COVID-19

Abstract: BackgroundThe effect of angiotensin-converting enzyme inhibitor/angiotensin receptor blockers (ACEI/ARB) on the COVID-19 remains controversial from clinic evidence. MethodsThis is a retrospective, two-center case series of 198 consecutive COVID-19 patients with a history of hypertension. ResultsAmong 198 patients, 58 (29.3%) and 16 (8.1%) were on were on ARB and ACEI, respectively. Patients who were on ARB or ACEI/ARB had a significantly lower rate of severe illness and ARDS when compared with patients treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The novel coronavirus disease-2019 (COVID-19) pandemic has presented great challenges in health care. [ 1 ] Research has shown that 58% of the patients with COVID-19 received corticosteroids therapy when they were hospitalized. [ 2 ] The usefulness and safety of corticosteroids as an adjuvant therapy for COVID-19 pneumonia remain controversial corticosteroids may diminish the inflammatory response, a major factor for lung damage and acute respiratory distress syndrome (ARDS) in viral respiratory tract infection.…”
Section: Introductionmentioning
confidence: 99%
“…The novel coronavirus disease-2019 (COVID-19) pandemic has presented great challenges in health care. [ 1 ] Research has shown that 58% of the patients with COVID-19 received corticosteroids therapy when they were hospitalized. [ 2 ] The usefulness and safety of corticosteroids as an adjuvant therapy for COVID-19 pneumonia remain controversial corticosteroids may diminish the inflammatory response, a major factor for lung damage and acute respiratory distress syndrome (ARDS) in viral respiratory tract infection.…”
Section: Introductionmentioning
confidence: 99%